2010
DOI: 10.1111/j.1095-8339.2010.01048.x
|View full text |Cite
|
Sign up to set email alerts
|

Wood and bark anatomy of Steganotaenia and Polemanniopsis (tribe Steganotaenieae, Apiaceae) with notes on phylogenetic implications

Abstract: The wood and bark structure of the distinctive southern African genera Polemanniopsis (including the newly described species P. namibensis) and Steganotaenia have been described. To allow for comparisons with the traditional subfamily Saniculoideae, a shrubby species of Eryngium from the Juan Fernández Islands was also studied. Polemanniopsis and Steganotaenia were recently considered as two closely related genera forming a new tribe Steganotaenieae of subfamily Saniculoideae (Apiaceae), whereas Eryngium is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Anginon , Dracosciadium , Glia , Heteromorpha and Polemannia show the presence of secretory canals in the cortex (Figs 6–8) and secondary phloem (Figs 18, 19, 21), the presence of two types of axial parenchyma (sheath parenchyma surrounding secretory canals and phloem parenchyma accompanying sieve tubes) and the absence of fibres in the secondary phloem. These bark characters are typical of the large majority of woody Apiaceae and all Araliaceae, Myodocarpaceae and Pittosporaceae (Van Tieghem, 1884; Metcalfe & Chalk, 1950; Kotina & Oskolski, 2010; Nilova & Oskolski, 2010; Oskolski et al ., 2010) examined to date (Fig. 22), with the exception of Centella L. (Mackinlayoideae, Apiaceae), which has no secretory canals in the secondary phloem.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anginon , Dracosciadium , Glia , Heteromorpha and Polemannia show the presence of secretory canals in the cortex (Figs 6–8) and secondary phloem (Figs 18, 19, 21), the presence of two types of axial parenchyma (sheath parenchyma surrounding secretory canals and phloem parenchyma accompanying sieve tubes) and the absence of fibres in the secondary phloem. These bark characters are typical of the large majority of woody Apiaceae and all Araliaceae, Myodocarpaceae and Pittosporaceae (Van Tieghem, 1884; Metcalfe & Chalk, 1950; Kotina & Oskolski, 2010; Nilova & Oskolski, 2010; Oskolski et al ., 2010) examined to date (Fig. 22), with the exception of Centella L. (Mackinlayoideae, Apiaceae), which has no secretory canals in the secondary phloem.…”
Section: Discussionmentioning
confidence: 99%
“…examined to date, whereas Steganotaenia Hochst. and Polemanniopsis B.L.Burtt belonging to tribe Steganotaenieae (subfamily Apioideae) are distinctive in having a diffuse type of secondary phloem dilatation (Kotina & Oskolski, 2007; Nilova & Oskolski, 2010; Oskolski & Van Wyk, 2010; Oskolski et al ., 2010). As for other families, the radial type of dilatation occurs throughout Pittosporaceae (Nilova & Oskolski, 2010), in most Myodocarpaceae and in early branching lineages of Araliaceae and in the Polyscias J.R.Forst.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although bark is one of the most conspicuous features of woody plants in the field, and despite several studies having shown its potential for improving phylogenetic relationships in many plant families (e.g., Metcalfe & Chalk, 1950a, b;Zahur, 1959;Esau, 1969;Richter, 1981;Roth, 1981;Esau & Cheadle, 1984;Archer & Van Wyk, 1993;Liu & Gao, 1993;Costa & al., 1997;Carlquist, 1991Carlquist, , 1996Carlquist, , 1998Carlquist, , 2005De Magistris & Castro, 2001;Castro & al., 2005;Olson, 2005;Schweingruber, 2006;Junikka & Koek-Noorman, 2007;Oskolski & al., 2007Oskolski & al., , 2010, bark is still one of the most poorly known plant tissues and therefore rarely included in systematic studies. There are three major reasons for the fragmentary knowledge of bark anatomical data.…”
Section: Introductionmentioning
confidence: 99%
“…The power of this type of approach, either alone or linked to molecular phylogenetics, in helping to develop our understanding of the relationships between plants is illustrated well by subject matter published recently in the Botanical Journal of the Linnean Society . Papers published cover extant groups of angiosperms (Banks, Himanen & Lewis, ; Bradshaw et al ., ; Carlquist, ; De Villiers, Tilney & Van Wyk, ; Lu et al ., ; Oskolski, Rossouw & Van Wyk, ; Pole, ; Ren, Chang & Endress, ; Xu & Ronse De Craene, ; Matthews & Endress, ; Zhang & Ren, ), gymnosperms (Rydin, Khodabandeh & Endress, ) and pteridophytes (Christenhusz, ; Lehtonen et al ., ) and extinct fossil taxa (Seyfullah et al ., ; Edwards & Axe, ). An earlier issue this year (with an editorial by Schönenberger & Von Balthazar, ) included several additional papers of this type.…”
mentioning
confidence: 99%